TEACHING LISTENING USING DUOLINGO APPLICATION - LIDYA MALDINI PUTRI; AULIA ISLAMIATI (IKIP Siliwangi, 2018)
Listening is one of the language skills that quite difficult to master. Listening to more attention and more concentration is needed than any other skill. Listening is different from hearing. Hearing refers to the ear that the voice enters. Physically process, depending on whether they have a hearing problem, which happens automatically. While listening not only give an attention to the story, but the way it is told, language, intonation, voice, and body language. The objective of this study entitled “Teaching Listening Using Duolingo Application” was to reveal whether or not using an application called Duolingo in English learning significantly improves students' listening skills. This research used pre-experimental design and quantitative research method. This study involves 799 consisting of 24 classes in SMKN 2 Karawang and the author takes only one class of 36 students in X- Tata Boga 3 Class. Furthermore, the data taken from pretest and posttest results to find out whether using Duolingo apps improves students' listening skills. The collected data were analyzed using SPSS 24 version. This study found that test of normality consist of the data of pretest is (0.076) and the data of posttest is (0.200) in 33 samples. In addition the value of Sig. (2-tailed) 0.000 because of the value of the Sig value. (2-tailed) < 0.005 it can be concluded that using Duolingo Applications can improve students' listening skills and also able to make the teaching list motivate students in learning English.Keywords: Teaching, Listening, Duolingo Application